Approximate solution of melt depth inside titanium during laser materials processing - Ngwenya, Dineo (Centre for Minerals Research, 2017)
The use of lasers has increased in areas of science, engineering and medicine. Their advantages over the traditional methods of thermal application are their ability to localize thermal treatments, ability to deliver high power density and to complete thermal processes in extremely short time periods. During the irradiation of a material, only a portion of the laser beam energy is absorbed. If the absorbed energy is high enough, melting can occur. The ability to predict, thus control the melting process is an advantage to manufacturing processes such as laser welding, surface re-melting and alloying. Using analytical approaches that are already in existence, this research adapts a mathematical model to approximate temperature profiles as well as isothermal depths given a single laser pulse. In order to assess the error associated with the adapted model, laser irradiation experiments are carried out on CP titanium samples using a focal spot of 600 μm and nitrogen gas as the shielding gas at a flow rate of 5 l/min. The effects of some important laser processing parameters on the melt depth are discussed. The adapted model approximated that the melt depth increases with both increasing laser power and increasing pulse duration. Furthermore, the experimental results revealed that it is the combination of short pulses and a high laser power that yields melt zones that are relatively free of porosity, craters and cracking. Additionally, an assessment of the error associated with the adapted model revealed that the adapted model generally overestimates the experimental data with increasing laser pulse duration. At a combination of 0.1s and 1200W (representing a combination of short laser pulse and high laser power) the error of approximation was 59%. The error increased to 90% at a combination of laser parameters 5s and 600W (representing a combination of a long laser pulse and low laser power). It is recommended that future studies be undertaken to improve modelling accuracies for a wider range of laser processing parameters.